The Impact of Using Balance Model in Teaching Linear Equation - Evans Atteh; Emmanuel Appoh Andam; Johnson Amoako; William Obeng–Denteh; Frimpong Wiafe (Archives of Current Research International, 2018)
The paper is an action research paper which involves a sample of thirty (30) second year students of Buasi Roman Catholic Junior High School. The aim of the study was to use the balance model approach in the teaching and learning of linear equations to enhance students’ conceptual understanding in the principles of solving linear equations in one variable. The data was gathered using tests. Prior to the study, it was observed that the learners’ were not able to understand and solve linear equations in one variable. Thus the balance model approach of teaching and learning was employed as the intervention strategy and was carried in a series of activities. The pre – test and post – test scores obtained by the students were recorded and analyzed quantitatively based on the research questions that preceded the study. Comparatively, the results obtained from the pre – test and post – test showed a significant improvement on the students’ ability to solve linear equations in one variable. The descriptive analysis of the tests’ results showed that the use of the balance model in teaching and learning of linear equations improves students’ understanding of the principles of solving linear equations in one variable. It was then concluded from the findings that the balance model approach of teaching and learning employed during the intervention processes improved the students’ academic achievements and it lead to an improvement in their performance.